Three-dimensional failure envelope of concrete dam shear keys. (15th October 2022) - Freitas, Mario; Ben Ftima, Mahdi; Léger, Pierre; Bouaanani, Najib
Highlights: Multiaxial nonlinear FE analyses of concrete dam contraction joint shear keys. Shear keys under free dilation condition fail at smaller loads than restrained ones. Interactions with bending and torsion significantly reduce shear key capacity. Ratio between moment or torsion and shear load controls failure mechanism. Load bearing capacity is highly dependent on shear key failure mechanism. Abstract: Shear keys provide interlocking mechanisms along the vertical contraction joints of many concrete gravity dams. The shear key ultimate shear capacity is typically estimated as a function of the friction and cohesion that could be mobilised across a 2D shear plane located at the base of the key when subjected to a normal confinement pressure, P. A two-dimensional response of dam monoliths and shear keys shearing-off at their bases, is assumed. However, evidence of 3D interlocking behaviour between dam monoliths and the possibility of different key failure mechanisms involving interacting axial, P, shear, V, moment, M, and torsion, T, indicates that typical empirical formulations could significantly overestimate the actual shear key capacity under floods and seismic loadings. This paper presents an evaluation of the load–displacement response of shear keys subjected to multiaxial loading via nonlinear finite element analyses. A concrete "Continuous Surface Cap Model" (CSCM), available in the computer program LS-Dyna, is first shown to best capture the experimental shear keys' ultimate and residual shear capacity responses among five constitutive models. The effects of the tensile strength, fracture energy, confinement pressure, friction coefficient, initial opening, and dilation conditions on the load–displacement response of keys are investigated. Failure envelopes considering the key multiaxial shear capacity with confinement pressure, P, moment, M, and torsion, T, are developed. The ratios between moment and shear, M/V, and torsion and shear, T/V, control the failure mechanism. Increasing these ratios significantly reduce the ultimate shear capacity.